Combining Ultrasound Pulse-Echo and Transmission Computed Tomography for Quantitative Imaging the Cortical Shell of Long-Bone Replicas - Shortell, Matthew P.; Althomali, Marwan A. M.; Wille, Marie-Luise; Langton, Christian M. (Frontiers in Materials, 2017)
We demonstrate a simple technique for quantitative ultrasound imaging of the cortical shell of long bone replicas. Traditional ultrasound computed tomography instruments use the transmitted or reflected waves for separate reconstructions but suffer from strong refraction artefacts in highly heterogenous samples such as bones in soft tissue. The technique described here simplifies the long bone to a two-component composite and uses both the transmitted and reflected waves for reconstructions, allowing the speed of sound and thickness of the cortical shell to be calculated accurately. The technique is simple to implement, computationally inexpensive and sample positioning errors are minimal.